2021
DOI: 10.1007/s10147-021-01935-7
|View full text |Cite
|
Sign up to set email alerts
|

4-step, 2-h carboplatin desensitization in Japanese patients with ovarian cancer: a prospective study

Abstract: Background Carboplatin is a key drug for ovarian cancer. However, it sometimes induces hypersensitivity reactions (HSRs) that result in the discontinuation of the treatment. Although various desensitization protocols have been reported in previous retrospective studies, a limited number of prospective studies have analyzed these protocols. Methods Patients with platinum-sensitive relapsed ovarian cancer who experienced carboplatin-induced HSRs were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Our findings are consistent with the results of previous studies. [14–19] In our study, OS2 (from the desensitization procedure) was 42.2 months (range: 25.3–59.1), and the 1-, 2-, and 5-year survival rates were 92.6%, 75.6% and 47.2%, respectively. Overall, these results support the effectiveness of CP-D in treating recurrent EOC.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Our findings are consistent with the results of previous studies. [14–19] In our study, OS2 (from the desensitization procedure) was 42.2 months (range: 25.3–59.1), and the 1-, 2-, and 5-year survival rates were 92.6%, 75.6% and 47.2%, respectively. Overall, these results support the effectiveness of CP-D in treating recurrent EOC.…”
Section: Discussionmentioning
confidence: 59%
“…In a prospective study conducted by Nishimura et al in 2021, a 4-step 2-hour rapid desensitization protocol was applied to 22 patients with 90.9% success, and ORR and OS were 63.6 months and 23.8 months, respectively. [18] An interesting aspect of that study was that no treatment-related deaths were observed in patients who developed a grade 3 reaction and were not treated with adrenaline. Similarly, our study showed that severe (grade 3) side effects, although observed less frequently, were controlled with fluid replacement and steroid and antihistamine treatment, without using adrenaline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experience, this approach identified a cross-reactivity between these platinum agents in 18% of cases and helped to identify an alternative therapeutic approach. Consequently, if the therapy with platinum is strongly indicated despite immediate-HSRs, the following treatment will be performed administering the platinum agent, following recent protocols of desensitization [23,[27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%